ESG as a Field of Power: The Relationship Between Strategic Management and Accounting Practices - Adrian Eka Darma Serang (Oikonomia : Journal of Management Economics and Accounting, 2026)
This study examines ESG as a field of power where strategic management decisions are translated and represented through accounting practices to construct organizational legitimacy. ESG has evolved from a reputational reporting tool into a strategic mechanism through which firms negotiate trust, authority, and long term value in response to investor, regulatory, and societal pressures. A qualitative interpretive case study design was employed using semi structured interviews with executives and accounting managers, alongside document analysis of ESG reports, annual reports, and internal strategic policies prepared under GRI and IFRS S frameworks. The findings reveal that ESG agendas are first shaped at the top management and board level through strategic priorities, risk governance, and investment decisions. These agendas are then operationalized through accounting metrics, KPIs, and disclosure narratives that define what is measurable and visible to stakeholders. The study shows that accounting serves not only as a reporting mechanism but also as an instrument of informational power, enabling selective representation of ESG performance. The results confirm that ESG legitimacy is co constructed through the interaction between managerial authority and accounting representation. This research concludes that understanding ESG requires examining the relational dynamics between strategic management and accounting practices rather than viewing ESG solely as a compliance or sustainability framework